TUGAS DAN KARAKTERISTIK STAF ADMINISTRASI PT. XX BERDASARKAN ANALISA JABATAN - Nurul Qomariyah (Universitas Gunadarma, 2014)
The aim of this study is to analyze the administration staff position in PT XX. Staff administration is one of the most crucial position in PT XX. Method use in this research are self-repport, interview and observation, dan document analysis. The participants of this research are six persons whose position in PT XX as an finance and administration supervisor, and the rest five persons are administration staffs. The result shows the overlapping job description and responsibility between the staffs. Beside this finding, there should be different job description between the position even though it is in the same level. Keywords: Job analysis, Job description, Job characteristics